Abordagem não farmacológica na hipertensão arterial sistêmica - Viviane Lemos Silva Fernandes; Walmir Jerônimo da Silva Júnior (UniEVANGÉLICA, 2012)
The study reported in this paper aimed to learn the perception of the UniEVANGÉLICA Medical School's faculty on the Problem-Based Learning Methodology (PBL). Regarding to the method used, a cross-sectional retrospective, descriptive field study with qualitative approach was conducted. Twenty faculty members of the Medical School were interviewed. The data showed that respondents, when asked about the use of the methodology in medical education, demonstrated positivity, indicating aspects such as humanization and greater need for performance by students in the knowledge building. 85% of the teachers interviewed believe the methodology is the best for training doctors with interpersonal and interprofessional skills, while 95% said that the methodology (PBL) requires more effort from the teachers acting in areas that are not exactly their field of expertise as far as tutoring is concerned. The conclusion was that the problem-based learning presents an innovative model for the learning building. Therefore, there are breaking in concept , historically built on the process of learning, and there are several challenges that the PBL methodology proposes to teachers and students.